2015
DOI: 10.1128/cvi.00324-15
|View full text |Cite
|
Sign up to set email alerts
|

IP-10 Is a Sensitive Biomarker of Antigen Recognition in Whole-Blood Stimulation Assays Used for the Diagnosis of Mycobacterium bovis Infection in African Buffaloes (Syncerus caffer)

Abstract: African buffaloes (Syncerus caffer) are maintenance hosts of Mycobacterium bovis, the causative agent of bovine tuberculosis. They act as reservoirs of this infection for a wide range of wildlife and domestic species, and the detection of infected animals is important to control the geographic spread and transmission of the disease. Interferon gamma (IFN-␥) release assays (IGRAs) utilizing pathogen-derived peptide antigens are highly specific tests of M. bovis infection; however, the diagnostic sensitivities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 15 publications
5
34
0
Order By: Relevance
“…14,[17][18][19] This study aimed to evaluate more cytokines as alternative biomarkers of whole-blood stimulation assays in diagnosing nonhuman Panel 1 6 TNF RII, IL19, RANTES, MIF, MPO, Galectin-3 Panel 2 37 IFN-γ, TNF-α, TNF RI, GM-CSF, IL1β, IL1RA, IL1 RII, IL2, IL2 Rα, IL4, IL5, IL6, IL6 Rα, IL8, IL10, IL15, IL17A, IL22, MCP-1, MIP-1β, MCP-3, MCP-4, CCL11, CCL18, CCL22, CCL27, CXCL1, CXCL4, IP-10, CXCL12, CXCL13, CD14, CD27, CD30 been proven to be robust biomarkers of whole-blood stimulation assays. [22][23][24] In our study, IFN-γ and IP-10 were also identified as sensitive markers for the PPD-based whole-blood stimulation assay in nonhuman primates, and IP-10 appeared to be more sensitive than…”
Section: Discussionsupporting
confidence: 51%
“…14,[17][18][19] This study aimed to evaluate more cytokines as alternative biomarkers of whole-blood stimulation assays in diagnosing nonhuman Panel 1 6 TNF RII, IL19, RANTES, MIF, MPO, Galectin-3 Panel 2 37 IFN-γ, TNF-α, TNF RI, GM-CSF, IL1β, IL1RA, IL1 RII, IL2, IL2 Rα, IL4, IL5, IL6, IL6 Rα, IL8, IL10, IL15, IL17A, IL22, MCP-1, MIP-1β, MCP-3, MCP-4, CCL11, CCL18, CCL22, CCL27, CXCL1, CXCL4, IP-10, CXCL12, CXCL13, CD14, CD27, CD30 been proven to be robust biomarkers of whole-blood stimulation assays. [22][23][24] In our study, IFN-γ and IP-10 were also identified as sensitive markers for the PPD-based whole-blood stimulation assay in nonhuman primates, and IP-10 appeared to be more sensitive than…”
Section: Discussionsupporting
confidence: 51%
“…While TSTs are the mainstays for bovine TB antemortem testing, blood-based tests are attractive, as they require only a single visit to the farm, provide the opportunity for immediate repeat testing, and yield results that are less subjective than those of TSTs. Additional biomarkers have recently emerged as potential candidates for use in blood-based TB tests for humans (reviewed by Walzl et al [5] and Salgame et al [6]) and cattle, including interleukin-1␤ (IL-1␤), IL-2, tumor necrosis factor alpha (TNF-␣), nitric oxide, IL-17, and IFN-␥-induced protein 10 (IP-10) (7)(8)(9)(10)(11)(12)(13). Of these, IL-17 is particularly appealing as a biomarker for bovine TB, as IL-17A mRNA responses determined using real-time quantitative PCR (RT-qPCR) may be predictive of both vaccine efficacy (11,14,15) and lesion severity (7) when measured after vaccination and infection, respectively.…”
mentioning
confidence: 99%
“…In both these species, IP-10 is produced in greater amounts than IFN-γ in antigen-stimulated whole blood and has been shown to be a more sensitive marker of mycobacterial infection [8, 9, 13]. In the present study, despite the use of ELISA antibodies produced against distantly related species, measurement of IP-10 proved to be a useful marker of immune activation.…”
Section: Discussionmentioning
confidence: 67%
“…In other species, such as cattle, in vitro tests of cell-mediated immunity (CMI) offer the most sensitive methods for TB diagnosis by detecting the release of interferon-gamma (IFN-γ) in response to mycobacterial antigens [6, 7]. Moreover, an alternative diagnostic marker of CMI, IFN-γ-inducible protein 10 (IP-10), has been shown to improve diagnostic sensitivity in humans and buffaloes ( Syncerus caffer ) [8, 9]. The specificity of such assays can be optimised by using highly specific antigens such as 6 kDa early secretory antigenic target (ESAT-6) and 10 kDa culture filtrate protein (CFP-10) [10, 11].…”
Section: Introductionmentioning
confidence: 99%